KERANGKA PEMBELAJARAN BERASASKAN PROSES KERJA KURIKULUM STANDARD KOLEJ VOKASIONAL (KSKV) DIPLOMA VOKASIONAL MALAYSIA - Abd Samad, Noorazman; Tuan Ahmad, Tuan Aidil; Ismail, Affero; Amiruddin, Mohd Hasril; Mohd Nor, Siti Nor Fazelah (Online Journal for TVET Practitioners, 2017)
The emphasis of the vocational education system at the school level is more focused on generating generic skills that are deemed to provide greater opportunities for vocational school leavers to further their studies or venture into the skills market based on their skills. However, it is disappointing that the services received by vocational school leavers are treated equally as those without basic occupational skills and they are also ignored and poorly esteemed by employers. This phenomenon raises the question whether our TVET delivery system is able to cater to the need to train and retrain fast knowledge workers with the ability to adapt skills in the workplace to meet the knowledge-based and market-based challenges. Based on these challenges, the Malaysian government has planned to transform Malaysia into a developed economics based on the Vocational College delivery system for post-15-year-old teens. The PBPK (WPBL) is a tool of how workers are studying and working according to the needs of their work world by constructing meaningful constructs, so that it is required by employees to understand all the skills of this work. How the task of identifying and explaining WPBL skills is not always easy. Progarm vocational preparations at the Vocational College level should also educate potential workers at the post-15’s age as a mature citizen, not just to the degree to which the skills can be learned. The basic concept of WPBL is active learning as workers solve problems in daily work routines. This paper proposes the need to look at the importance of working knowledge processes that can be applied to the Vocational College program in Malaysia